Cost and benefits of climate change adaptation policies: evidence from an RCT and extreme flooding in Pakistan - Avdeenko, Alexandra; Frölich, Markus (Journal of the European Economic Association, 2025)
A significant component of the cost of climate change is the investment required for adaptation programs. Effective adaptation strategies are becoming essential for managing the negative economic impacts of climate change. In this study, we estimate climate change damage costs that incorporate adaptation costs and benefits under different environmental scenarios. Over a 3-year period, we tracked households in rural Sindh, some of which experienced extreme monsoon flooding in 2016. We present how targeted climate adaptation measures can be effective in mitigating adverse climate effects and fostering resilience. Compared to a randomly selected control group, communities participating in a humanitarian aid preparedness program demonstrated significant improvements in food security and health outcomes after experiencing the negative weather shock. A cost-benefit analysis shows that the adaptation investments pay for themselves after a short period of time and have the potential to considerably reduce the social costs of carbon if a longer time horizon is considered. This paper contributes to the climate change literature by demonstrating how estimates from field experiments can be used to update the costs of climate change projections, while also highlighting the limitations of this approach.